Respuesta :

Answer:

Option B

Step-by-step explanation:

Please see attached picture for full solution.

Ver imagen Leora03

Answer:

B

Step-by-step explanation:

Using the rule of radicals

[tex]\sqrt{a}[/tex] × [tex]\sqrt{b}[/tex] ⇔ [tex]\sqrt{ab}[/tex]

The area (A) of a triangle is calculated as

A = [tex]\frac{1}{2}[/tex] bh ( b is the base and h the perpendicular height ), thus

A = [tex]\frac{1}{2}[/tex] × [tex]\sqrt{21y}[/tex] × [tex]\sqrt{3y^5}[/tex]

   = [tex]\frac{1}{2}[/tex] × [tex]\sqrt{63y^6}[/tex]

   = [tex]\frac{1}{2}[/tex] × [tex]\sqrt{63}[/tex] × [tex]\sqrt{y^6}[/tex]

   = [tex]\frac{1}{2}[/tex] × [tex]\sqrt{9(7)}[/tex] × [tex]\sqrt{(y^3)^2}[/tex]

   = [tex]\frac{1}{2}[/tex] × 3 × [tex]\sqrt{7}[/tex] × y³

   = [tex]\frac{3}{2}[/tex] y³[tex]\sqrt{7}[/tex] → B

ACCESS MORE